2015
DOI: 10.1002/dvg.22905
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin‐2 genomic elements drive cre recombinase expression in primitive blood, vascular and neuronal lineages

Abstract: We have established a novel Cre mouse line, using genomic elements encompassing the Nrp2 locus, present within a bacterial artificial chromosome clone. By crossing this Cre driver line to R26R LacZ reporter mice, we have documented the temporal expression and lineage traced tissues in which Cre is expressed. Nrp2-Cre drives expression in primitive blood cells arising from the yolk sac, venous and lymphatic endothelial cells, peripheral sensory ganglia, and the lung bud. This mouse line will provide a new tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, EMPs can arise in the absence of hemodynamic forces from blood flow, which initiates shortly after E8 and is essential for later arterial-venous specialization of yolk sac vessels (le Noble et al, 2004;Lucitti et al, 2007;Lux et al, 2008). Lineage tracing studies using EC-specific genes including Nrp2 (expressed in non-arterial ECs) and Lyve1 (expressed in yolk sac ECs and lymphatic vascular beds) support the notion that EMPs are generated from HE unique from precursors of both the earlier primitive wave of hematopoiesis in the yolk sac and from later waves of intra-embryonic hematopoiesis giving rise to HSCs (Wiszniak et al, 2015;Lee et al, 2016).…”
Section: Erythromyeloid Progenitors Arise From Hemogenic Endothelium mentioning
confidence: 84%
“…Furthermore, EMPs can arise in the absence of hemodynamic forces from blood flow, which initiates shortly after E8 and is essential for later arterial-venous specialization of yolk sac vessels (le Noble et al, 2004;Lucitti et al, 2007;Lux et al, 2008). Lineage tracing studies using EC-specific genes including Nrp2 (expressed in non-arterial ECs) and Lyve1 (expressed in yolk sac ECs and lymphatic vascular beds) support the notion that EMPs are generated from HE unique from precursors of both the earlier primitive wave of hematopoiesis in the yolk sac and from later waves of intra-embryonic hematopoiesis giving rise to HSCs (Wiszniak et al, 2015;Lee et al, 2016).…”
Section: Erythromyeloid Progenitors Arise From Hemogenic Endothelium mentioning
confidence: 84%
“…Additionally, during avian blood vessel development, NRP1 is predominantly expressed in the arteries whereas NRP2 is expressed in the veins [ 110 ]. Furthermore, by crossing mice containing Cre recombinase driven by the NRP2 locus with a ROSA26-LacZ reporter line, researchers have demonstrated that at E12.5, NRP2 is expressed mainly in the venous vasculature, while NRP1 expression is more arterial [ 111 ]. Interestingly, in vitro analyses of rabbit VSMCs demonstrated that venous VSMCs display a more de-differentiated phenotypic state and exhibit increased proliferative and synthetic activity in comparison to arterial VSMCs [ 112 ].…”
Section: Vsmc Phenotypic Switchingmentioning
confidence: 99%